How to Begin with Dental Implants - Shah, Rohit; John, Ligi Elsa; Mitra, Dipika; Rodrigues, Silvia; Mhamunkar, Priyanka; Vijayakar, Harshad (International Journal For Research In Health Sciences And Nursing, 2018)
Dental implant - A surgical component that is placed within the bone of the jaw to support a dental prosthesis such as a crown, bridge or removable denture. A surgical procedure is required to place the dental implant inside the jawbone. One or more implants may be required for a specific case.